Analysis on the Effectiveness of Extract Mixture of Anthouse Plant (Myrmecodia Pendans) and Red Pepper Vine (Piper Ornatum) as a Green Corrosion Inhibitor on the Corrosion Rate of API 5L Grade B Steel in H2SO4 1M Solution - Tubagus Noor Rohmannudin; Agung Purniawan; Sulistijono -; Bintang Ayu Nuraeni (International Journal of Industrial Research and Applied Engineering, 2018)
The analysis of the mixture of anthouse plant (Myrmecodia pendans) and red pepper vine (Piper ornatum) in H2SO4 1M solution had been studied by weight loss, Electrochemical Impedance Spectroscopy (EIS), Fourier-Transform Infrared Spectroscopy (FTIR), and Spectrometer test. The Myrmecodia pendans and Piper ornatum were chosen because they contain antioxidants that can inhibit the corrosion rate. The specimen used in this study was API 5L Grade B steel in H2SO4 1M solution. The compositions used in this study were 100% MP : 0% PO, 75% MP : 25% PO, 50% MP : 50% PO, 25% MP : 75% PO, and 0% MP : 100% PO (MP: Myrmecodia pendans, PO: Piper ornatum). FTIR testing result shows that a passive layer was formed by O, H, and N bonds. The weight loss method shows that the highest efficiency of 52.43% was achieved by 50% MP : 50% PO mix composition. Polarization testing shows that the corrosion rate decreased drastically with the addition of 50% MP : 50% PO mix composition, i.e., from 36.32 mpy to 7.93 mpy, due to the passive layer formed on the steel surface. EIS results show the presence of resistance solution (Rs), charge transfer resistance (Rct), and CPE. The adsorption free energy value of the mixture of Myrmecodia pendans and Piper ornatum was −10.02 kJ/mol and it was a physical adsorption.